Keberhasilan Konseling ditinjau dari Self-Disclosure Klien: Studi pada Klien yang Berasal dari Indonesia - Putra, Ade Herdian; Mudjiran, Mudjiran (Universitas Negeri Padang, 2023)
Successful counseling is characterized by positive feelings, positive thoughts, and positive client behavior after counseling. However, not all counseling sessions can be successful. One of the causes that are predicted to hinder the success of counseling is the low self-disclosure of clients in counseling sessions. This study aims to examine the correlation between client self-disclosure and counseling success. This study uses a quantitative approach with correlational methods. The participants in this study were 204 clients from Indonesia who attended counseling within the last six months. The instruments used in this study were the client's self-disclosure scale and the counseling success scale. Research data was collected in the range March-June 2023. Analysis of research data used descriptive statistical analysis and partial least squares. The results of this study indicate that, in general, the level of self-disclosure of Indonesian clients and the success rate of counseling in Indonesia are in the very high category. Furthermore, the results of this study show that client self-disclosure has a positive and significant correlation with counseling success. Both the counselor and the client must consider the client's self-disclosure before starting a counseling session to prevent a low success rate of counseling.